Too many cooks?: committees in monetary policy - Helge Berger; Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2008)
How many people should decide about monetary policy? In this paper, we take an empirical perspective on this issue, analyzing the relationship between the number of monetary policy decision-makers and monetary policy outcomes. Using a new data set that characterizes Monetary Policy Committees (MPCs) in more than 30 countries from 1960 through 2000, we find a U-shaped relation between the membership size of MPCs and inflation; our results suggest that the lowest level of inflation is reached at MPCs with about seven to ten members. Similar results are obtained for other measures, such as inflation variability and output growth. We also find that MPC size influences the success of monetary targeting regimes. In contrast, there is no evidence that either turnover rates of MPC members or the membership composition of MPCs affect economic outcomes.
Keywords: E52; E58; E61; 330; central bank design; monetary policy committee; central bank board; central bank council; governance; inflation; Zentralbank; Geldpolitik; Gruppenentscheidung; Inflationsbekämpfung; Welt